2021
DOI: 10.54783/ijsoc.v3i1.285
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Reasoning Abilities of High School Students in Solving Contextual Problems

Abstract: The purpose of this study was to describe students’ mathematical reasoning abilities, such as: drawing conclusions from a statement, doing mathematical manipulation, providing valid arguments and presenting mathematical statements, both verbally and in writing, in the form of pictures or graphs. This research used the descriptive qualitative method. The instruments used in this study were the main instrument (researchers) and the supporting instruments (tests and interviews). The test was given to 25 students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…The three subjects have made mathematical statements appropriately from relevant concepts although there are still subjects who do not make reasons for each proof. This shows that the subject's procedural ability is good so that it supports the complex proof process (Firdausy et al, 2021;Jeannotte & Kieran, 2017).…”
Section: Discussionmentioning
confidence: 83%
“…The three subjects have made mathematical statements appropriately from relevant concepts although there are still subjects who do not make reasons for each proof. This shows that the subject's procedural ability is good so that it supports the complex proof process (Firdausy et al, 2021;Jeannotte & Kieran, 2017).…”
Section: Discussionmentioning
confidence: 83%
“…according to the question of section (a) which asks how the process is calculated. In fact, a person's reasoning ability can be seen from the way he performs mathematical manipulations, presenting answers both orally and in writing precisely (Firdausy & Indriati, 2021). ability (Solomon, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Then the results of other recent survey such as from TIMSS in 2015 showed that Indonesia's average score and ranking in the mathematics category was still very far from the international average score and was still in the backward rank. The international average score was 500 while Indonesia only reached on 397 (Firdausy et al, 2021). In the TIMSS version, Indonesia was ranked 44th out of 49 countries in the mathematics category (Firdausy et al, 2021).…”
mentioning
confidence: 98%